FcαRI Dynamics Are Regulated by GSK-3 and PKCζ During Cytokine Mediated Inside-Out Signaling - ten Broeke, Toine; Honing, Henk; Brandsma, Arianne M.; Jacobino, Shamir; Bakema, Jantine E.; Kanters, Deon; van der Linden, Jan A. M.; Bracke, Madelon; Koenderman, Leo; Leusen, Jeanette H. W. (Frontiers in Immunology, 2019)
IgA binding to FcalphaRI (CD89) is rapidly enhanced by cytokine induced inside-out signaling. Dephosphorylation of serine 263 in the intracellular tail of FcalphaRI by PP2A and PI3K activation are instrumental in this process. To further investigate these signaling pathways, we targeted downstream kinases of PI3K. Our experiments revealed that PI3K activates PKCzeta, which subsequently inhibits GSK-3, a constitutively active kinase in resting cells and found here to be associated with FcalphaRI. We propose that GSK-3 maintains FcalphaRI in an inactive state at homeostatic conditions. Upon cytokine stimulation, GSK-3 is inactivated through a PI3K - PKCzeta pathway, preventing the maintenance of phosphorylated inactive FcalphaRI. The concomitantly activated PP2A is then able to dephosphorylate and activate FcalphaRI. Moreover, FRAP and FLIP studies showed that FcalphaRI activation coincides with an increased mobile fraction of the receptor. This can enhance FcalphaRI valency and contribute to stronger avidity for IgA immune complexes. This tightly regulated inside-out signaling pathway allows leukocytes to respond rapidly and efficiently to their environment and could be exploited to enhance the efficacy of future IgA therapeutics.